STRUKTUR DAN MAKNA RITUAL MANDI PANCOR ADAT DAYAK SAWE DI SEKADAU HULU - Teresia Litta; Herlina (Hunatech Vol. XXX, No. XXX, 2023)
Sawe tribe is one of the Dayak tribes in Sekadau Regency. This research aims to explain oral literature, especially the pancor bathing ritual of the Dayak Sawe tribe's wedding tradition. The author will analyze the structure and meaning of the pancor bathing ritual. The research method used in this research is qualitative. Descriptive research form. The approach used in this research is structural. Based on research that has been carried out, the pancor bath is a traditional wedding ritual for the Sawe Dayak Tribe in the Regency. This traditional ritual is carried out as a condition for marriage in the Sawe tribe. Apart from that, this ritual is carried out based on the community's belief that bathing in pancor can relieve the bride and groom from bad luck and danger. So, the pancor bathing ritual is a traditional wedding ritual of the Sawe Tribe which must be maintained by the Dayak Sawe Tribe community so that it doesn't just disappear and the younger generation can learn about the pancor bathing custom.